Munchy Monster: Using video gaming to objectively evaluate front‐of‐pack labelling strategies for school‐aged children. Issue 8 (20th June 2019) - Becker, Mark W.; Brunk, Eric; Cwiakala, Katie; Bix, Laura
Abstract : Marketers have long targeted children in an attempt to influence food purchases. This is not the case for regulators; nutrition information is complex, using decimal places, percentages, and units of measure. It has been suggested that the approach to nutrition labelling in the United States is difficult for some adults to interpret, let alone children. This is unfortunate as children influence purchase decisions and childhood is a critical time for developing long‐lasting eating habits. An alternative approach to traditional nutrition labelling employs the use of front‐of‐pack (FOP) nutrition labels. FOPs provide simplified, truncated nutrition information on the front of packages. The objective of this work was to evaluate how four different FOP label designs impact the ability of children to assess product healthfulness and time to assessment. Children aged 6 to 10 played a video game where they fed "Munchy Monster" the healthier of two products. The principal display panels (PDPs) of two mock brands of cereal appeared together on a computer screen, and children were instructed to feed Munchy Monster the healthier of the two options as quickly as they could by pressing one of two arrows. Across trials, the FOP format varied in a 2 (colour/no colour) × 2 (facial icon/no facial icon) factorial design. Within a trial, both cereals presented the same FOP format, with one healthier than the other. Two groups of children participated in trials; those in the uninstructed group were simply asked to feed the monster the healthier cereal (n = 38); the "minimally instructed group" (n = 41) was told that "this part of the package" (the FOP) might help you decide which is healthier." Accuracy of selection and time to selection were dependent variables. With regard to accuracy, both groups showed evidence of a significant face by colour interaction ( P  < .001), with the colour or facial icon presence improving accuracy. For uninstructed participants, accuracy of selection significantly improved with any combination of colour or facial icon, and all other labels were improved when accuracy was compared with the treatments with no face/no colour, but none containing colour and/or facial icons differed from one another. Minimally instructed participants were also more accurate in identifying the healthier product for all FOP label designs compared with the no face/no colour condition ( P  < .001). However, the trials with FOPs including both face with colour also performed better than the face with no colour label, P  = .001. A main effect of colour was evident for both groups when time to correct selection was the dependent variable ( α  = .01). Results demonstrated that colour coding and/or facial icons significantly benefit selection accuracy and speed, particularly for the youngest children. Minimal training further improved accuracy and speed of responses. FOPs that leverage visual indicators assist even young children in assessing the nutritional value of a product. This should be considered as FOPs are debated and standard practices regarding these labels emerge. Abstract : Front of pack (FOP) labels have shown demonstrated, positive results regarding attention, comprehension and selection of healthier choices in adults. Their potential impact for children has yet to be studied. Herein, we using a video game strategy to investigate FOPs of four designs with children aged 6–10.